Transarterial Chemoembolization Combined With Radiofrequency Ablation Versus Hepatectomy for Hepatocellular Carcinoma: A Meta-Analysis - Dan, Yuan; Meng, Wenjun; Li, Wenke; Chen, Zhiliang; Lyu, Yongshuang; Yu, Tianwu (Frontiers in Surgery, 2022)
Background: Although many studies reported the effectiveness of transarterial chemoembolization (TACE) combined with radiofrequency ablation (RFA) or surgical resection (SR) in the treatment of hepatocellular carcinoma (HCC), the efficacy between these two strategies remains controversial. Therefore, this meta-analysis aimed to evaluate and compare the efficacy of sequential use of TACE plus RFA (TACE+RFA) and SR alone in the treatment of HCC. Methods: Relevant studies with unmatched and propensity score-matched patients were identified by comprehensive searches of the MEDLINE, PubMed, EMBASE, Web of Science, and Cochrane electronic databases. Meta-analysis was conducted using Review Manager (RevMan) software version 5.4.1. Finally, 12 eligible studies were included in this study, including 11 case-control studies and 1 randomized controlled trial. The primary outcome of interest for this study was to compare the 1-, 3- and 5-year overall survival (OS) and disease-free survival (DFS), major complications, 5-year OS in different tumor diameter between the two treatment strategies, and hospital stay time. Results: HCC patients who received TACE+RFA had lower incidence of complication rates and hospital stay time than those received SR alone. Among these studies using propensity score-matched cohorts, SR had better 3-year OS and 5-year OS than TACE+RFA, whereas there were no significantly differences between TACE+RFA and SR regarding the 1-year DFS, 3-year DFS, and 5-year DFS. When the tumor diameter is longer than 3 cm, the 5-year OS rate is better when SR is selected. Conclusion: There was no significant difference in the short-term survival outcomes between TACE+RFA and SR in HCC patients. Moreover, SR is superior to TACE+RFA in terms of long-term benefit effects, but may result in a higher risk of major complications and a longer hospital stay time.